PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA GURU SMP NEGERI 33 BANDAR LAMPUNG - Ristra Astriani (e-JKPP, 2019)
The Quality of education will produce the next generation that is superior and competitive. In order to realize quality of education, it is completed with optimal teacher performance. The aim of this study is to find out the influence of compensation and motivation towards teachers’ performance at SMPN 33 Bandar Lampung. This research used a survey method and quantitative data analysis. Based on the results of the research, the results is there is an influence between compensation and motivation towards teacher’s performance at SMPN 33 Bandar Lampung. This is considered by the determination coefficient of 55.8% and the remainder is determined by other factors. Next, the R value is 0.747 indicates that the correlation or relationship of the variable compensation, motivation and performance of the teacher has a positive relationship with a high level of correlation.. Based on the results of the research, the researchers gave suggestions such as, SMPN 33 Bandar Lampung needs to provide more compensation than before to improve teachers’ performance, SMPN 33 Bandar Lampung needs to improve teachers’ motivation factor to improve their performance and SMPN 33 Bandar Lampung provides sufficient to support learning activities.